Ekaristi Menurut Berthold Anton Pareira dalam Konteks Misa Live Streaming di Tengah Pandemi Covid-19 - Jegaut, Siprianus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
Focus of this study is to discuss “Pandemic and the meaning of the Eucharist, a theological review according to Berthold Anton Pareira and its contribution to Catholics who celebrate it in the form of live streaming amid covid 19.” The Eucharist celebrates mystery. That is what the Church stated succinctly, densely and majestically after the consecration. This cry was answered aloud by the people “We declare your death, glorify Your resurrection, until You come.” Other exclamations in this celebration such as “The gospel of God, etc. have all plunged us into mystery. We are led into the Spirit of Christ. He animates and heals us. The Eucharist forms the Church which is ushered to life by mystery. This study aims to what extent the experience of the faithful celebrating the Eucharist in the form of live streaming in the midst of the Covid 19 situation. The methodology used is the phenomenological method of experiencing the reality of the faithful. This study found, first, the Eucharist as the breath of life for believers. Second eucharists are a form of solidarity. Third, the Eucharist is the home of true brotherhood.